University Courses as Goods: How to Optimize Portal Information Architecture using Faceted Search - Peter Murár (Communication Today, 2025)
The article deals with the issue of new information architecture for the main section of the Slovak universities’portal. This portal has existed for nine years and is based on traditional portal conventions: a broad structure and many services. Such features alone are insufficient for present-day browsing. These portals and their logic are thus definitely past their time as user behaviour has changed considerably. Two goals were defined in order to advance the concept. First, the information architecture had to be simplified in order to ease the process of locating published information. Second, the information architecture had to be easy to scale as developers were already planning additional expansions to services. The redesign was based on the results of user research. Research involved interviews with six secondary school graduates and open card sorting with further seventeen secondary school graduates. We explored the ways in which students obtained information about their upcoming studies and the manner in which they expected such information to be arranged on a Web site; we also observed the way they used the Web site in real life. This initial user testing confirmed the importance of remodelling the current information architecture as finding the desired information on the current site is quite difficult. The primary issues are: a) a complicated hierarchy that does not match the way in which users locate information; b) some important information is not found where users look for such information; and c) some pages are overloaded by too much information. The hierarchy of the new information architecture places emphasis on the role of searching. Taking a broader, more current perspective, we realised that university studies and shopping online may indeed share many similarities. The selection process demands a reduction in the set of potential results and examining and obtaining detailed information about promising options. Building the information architecture of an academic Web site using faceted search may be a smart way to minimise the number of steps required to access the desired information and to keep the current taxonomy of universities studies intact as well.